Nanostructure controlled anti-cancer drug delivery using poly(ε-caprolactone) based nanohybrids - Singh N.K.; Singh S.K.; Dash D.; Das Purkayastha B.P.; Roy J.K.; Maiti P. (My University, 2025)
We have focused on the generation of various nanostructures of poly(ε-caprolactone) (PCL) using surface modified layered silicate. The improved and diverse mechanical, thermal and surface properties have been explored depending upon the nanostructure of the nanohybrids. The incorporation of drug into those nanohybrids further alters the nanostructure and subsequent properties. The rate of biodegradation has been studied in detail, with plausible mechanisms in different enzyme media being suggested, their specificity and the tunability of the biodegradation rate was demonstrated, followed by their optimization. The scaffolds of PCL and its nanohybrids with and without drugs have been prepared through electrospinning to control the dimensions of the nanofibers and their controlled degradation. The in-depth studies of the biocompatibility in terms of cell adhesion, genotoxicity and hemocompatibility have been performed to verify the suitability of the nanohybrids for potential biomedical applications. The biocompatibility of the nanohybrids at the gene level has been tested by the subcellular localization of an important regulator of pro-apoptotic signalling cascade, HIPK2 in human epithelial cells, demonstrating the attuned nature of the particles under study within the biological system. The blood compatibilities of the pure PCL and its nanohybrids were studied by platelet aggregation, platelet adhesion, and in vitro hemolysis assay, elucidating the excellent hemocompatibility of the novel nanohybrids. Biocompatible and hemocompatible nanohybrids have been testified for drug delivery and show sustained and controlled release of anti-cancer drugs (dexamethasone) in the presence of two dimensional disc-like nanoparticles. Hence, the developed nanohybrids are a potential biomaterial, suitable for tissue engineering and drug delivery. © 2012 The Royal Society of Chemistry.